Optimization of the Disclosure of Curanmor Crime to Increase Crime Clearance in Unit 5 of Satreskrim Polrestabes Semarang - Raka, Andhika (Advances in Police Science Research Journal, 2024)
This study aims to analyze the actions taken by Unit 5 in the process of disclosing the crime of motor vehicle theft as well as various other matters that affect the process of disclosing the criminal act of motor vehicle theft an effort to optimize the performance of Unit 5 Satreskrim in disclosing the criminal act of motor vehicle theft in the jurisdiction of the Semarang Polrestabes. This research itself uses qualitative methods and the research object is Unit 5 of the Criminal Investigation Unit of the Semarang Police. This research will use data collected through interviews, observation, and literature studies. This research has two problems in the process of optimizing the disclosure of criminal acts of theft in the form of organizational and management resources at Unit 5 of the Satreskrim Polrestabes Semarang. The field of organizational resources includes four management factors Man, Money, Material, and Method. Meanwhile, in the field of management itself, we will see four management functions namely Planning, Operating, Actuating, and Controlling. Research conducted by the authors found that with the existence of technology, supervision can be carried out remotely so that it can accelerate the disclosure of criminal cases of theft. However, there are still obstacles in disclosing cases, such as the lack of information obtained and the lack of available facilities and infrastructure which of course affects the performance of Unit 5 of the Semarang Polrestabes Criminal Investigation Unit. Based on this, efforts must be made in improving crime clearance to improve coordination between Unit 5 of the Semarang Polrestabes Criminal Investigation Unit and related agencies, increase outreach to the public about the importance of reporting crime cases, improve the quality of human resources, and improve the facilities and infrastructure available. In conclusion, this study shows that the use of technology can help in increasing the disclosure of the crime of theft, but other efforts are still needed to increase the overall crime clearance.